Did the millennium development goals work? : meeting future challenges with past lessons - Besada, Hany; Polonenko, Leah McMillan, 1982-; Agarwal, Manmohan (Policy Press, 2017)
Leading scholars and practitioners from a range of backgrounds and regions use area-specific case studies to critically assess the Millennium Development Goal (MDG) project and its impact.